Comparative Study of Numerical Schemes for Granular Combustion of Boron Potassium Nitrate - Annie Rose Elizabeth; Sumit Sarma; T. Jayachandran; P. A. Ramakrishna; Mondeep Borthakur (Aerospace, 2024)
Multiple applications in aerospace utilize pyrotechnic charges for their operation, and these charges are predominantly in the form of granules. One of the most used charges is boron potassium nitrate (BPN), and the present study focuses on mathematically modeling granular combustion, its experimental recreation, and carrying out a comparative study on three upwind schemes for its numerical simulation. A customized version of the seven-equation compressible multifluid formulation is presented in this paper to model granular combustion mathematically. Three upwind schemes, namely HLLC, AUSM+-up, and HLLC-AUSM, are used for the numerical comparison. Utilizing these, an axisymmetric code is developed for the comparative study. To experimentally replicate granular combustion, granular BPN is fired in a closed bomb test facility, and the experimental pressure history is used for the numerical comparisons. The developed code can adequately predict the physics of granular combustion, and all three schemes are equally capable of numerical prediction.